2001
DOI: 10.1016/s0006-3495(01)75903-6
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Propagation of Ca2+ Release during Excitation-Contraction Coupling in Atrial Myocytes

Abstract: Fast two-dimensional confocal microscopy and the Ca(2+) indicator fluo-4 were used to study excitation-contraction (E-C) coupling in cat atrial myocytes which lack transverse tubules and contain both subsarcolemmal junctional (j-SR) and central nonjunctional (nj-SR) sarcoplasmic reticulum. Action potentials elicited by field stimulation induced transient increases of intracellular Ca(2+) concentration ([Ca(2+)](i)) that were highly inhomogeneous. Increases started at distinct subsarcolemmal release sites space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
155
3
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(189 citation statements)
references
References 31 publications
(46 reference statements)
25
155
3
6
Order By: Relevance
“…This means that action potentials can only trigger Ca 2+ entry and CICR at the outer edge of an atrial myocyte. The distribution of RyRs in adult atrial cells appears to be similar to that in ventricular myocytes [10][11][12]. However, there is an important functional difference.…”
Section: Introductionmentioning
confidence: 75%
“…This means that action potentials can only trigger Ca 2+ entry and CICR at the outer edge of an atrial myocyte. The distribution of RyRs in adult atrial cells appears to be similar to that in ventricular myocytes [10][11][12]. However, there is an important functional difference.…”
Section: Introductionmentioning
confidence: 75%
“…2A, the spacing between rings of Ca 2+ release sites is 1 μm inside the cell, with a 2 μm gap to the peripheral junctional ring of Ca 2+ release sites. The 2 μm gap was adopted into the model because studies have shown such a discontinuity in the expression of RyR clusters (10,12,13). The physiological reason for this gap in atrial RyR distribution is not known.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the antibody labeling reports the presence of the RyR epitope (5) and thereby avoids any uncertainty as to the possible identification of electron densities within EM thin sections. Although some previous studies (6,7) have looked at the RyR distribution with fluorescence microscopy in the rat, no comparable data are available for human myocytes to our knowledge. Our data suggest that the reported fluorescencederived intercouplon distances are generally too large and provide 3D data sets of RyR distribution in rat and human ventricular myocytes.…”
mentioning
confidence: 98%